SURFACE ELECTRIFICATION OF ROCKS AND CHARGE TRAPPING CENTERS - Takeuchi A.; Hashimoto T.; Nagahama H. (My University, 2004)
In order to elucidate mechanisms of seismo-electromagnetic phenomena such as earthquake luminosity, earth potential changes, electromagnetic radiation and ionosphere disturbances, numerous fracture or frictional slip tests using rock samples have been conducted. Fracturing or frictional slipping generates electrification on the affected surfaces. The surface structures and gouges thus generated are generally disordered containing many charge trapping centers, which are important to understand surface electrification. To investigate the state changes of charge trapping centers in surface disordered layers, we measured thermoluminescence (TL) from milled quartz grains with and without surface disordered layers. The TL intensity per unit mass of the quartz decreased with decreasing grain diameter. Moreover, the TL intensity of samples with surface disordered layers decreased with grain diameter more rapidly than of those without such layers. This diameter-dependence can be explained by disturbances of TLs on the grain surfaces and by deformations of Al-hole centers in the surface disordered layers. Al-hole centers release holes as well as the newly formed E′ centers in surface disordered layers release electrons. Charges released from charge trapping centers are disturbed in the surface disordered layers during milling. Like milling, fracturing or frictional slipping could generate charge. These charges express themselves on the fractured or frictionally slipped surfaces as surface electrification. On the geological scale, fault zones are characterized by fracturing and frictional slipping. Therefore, the releases of charges from charge trapping centers in surface disordered layers within faults might provide a mechanism to explain seismo-electromagnetic phenomena.
Keywords: Seismo-electromagnetic phenomena; Surface disordered layer; Charge trapping center; Thermoluminescence (TL); Al-hole center